ANALISIS KOMPETENSI GURU PAI DAN MODUL AJAR YANG DIGUNAKAN DALAM MELAKSANAKAN KEGIATAN PEMBELAJARAN SESUAI KURIKULUM MERDEKA DI SMAN 6 KEPAHIANG - Saidil Mustar; Sunarsih Sunarsih; Selfia Melinda; Sinta Ramadhani (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2024)
This study aims to analyze (1) Professional Competency of PAI Teachers, (2) Teaching Modules of PAI and Ethics, (3) Learning Activities of PAI and Ethics According to the independent curriculum studied at SMAN 6 Kepahiang. This study uses a descriptive qualitative research approach. Data collection techniques are carried out by means of observation, interviews, and documentation. The data analysis technique uses the Miles and Huberman model with four stages namely; data collection, data condensation, data presentation, and conclusion drawing or data verification. The validity of the data using triangulation techniques. The results of the study show that (1) the Professional Competence of PAI Teachers at SMAN 6 Kepahiang has been implemented optimally. This can be seen from the indicators of professional competence that the teacher has, namely mastery of the material, use of relevant learning media, and being able to carry out evaluations of students. (2) The independent study-based PAI and Budi Pekerti teaching modules at SMAN 6 Kepahiang, the school forms a PAI and Budi Pekerti teacher team to carry out coordination, student involvement is carried out during research in each class at the first meeting. The PAI Teacher Team and Budi Pekerti also compiled an educational calendar, Prota, Promes, RPP based on the school curriculum and syllabus from the National Education Office and the Ministry of Religion-PAIS. (3) SMAN 6 Kepahiang in carrying out the Learning of Islamic Religious Education and Characteristics, the school did not intervene between the teacher and students, so that the learning environment at the end took place effectively. Teachers and students in implementing classroom learning emphasize the importance of material objectives, independence, and application to everyday life.